A műszaki innováció néhány földrajzi jellemzője Magyarországon - Nemes Nagy, József; Ruttkay, Éva (Tér és Társadalom, 1987)
In the introduction the authors review the main factors that influence the spatial diffusion of innovations: the location of innovation centres, the role of adaptability in application, and the communication network between innovators and users. Ön the basis of the analysis of about 1,300 Hungarian technical innovations, the authors point out the extremely strong concentration of innovating activities in certain regions, particularly in Budapest. 63% of the innovations under consideration were elaborated in the capital itself, and the share of Budapest in the innovations patented abroad is even greater. The sample shows that out of the total number (more than 3,000) of Hungarian settlements 63 produced some kind of innovation. Despite the extremely strong regional concentration of such activities, it is not the regional decentralization of innovation centres that is considered to be the most important path of development by the authors. They maintain that the infrastructural backwardness has to be decreased. Infrastructure serves as a basis for the innovation process: without a well-developed transport and communication system it is not possible to have a more decentralized network that would operate properly. The development of the infrastructure is also a precondition of an acceleration of innovation diffusion and a more proportionate distribution of the users. This path of development deserves special attention because it is the development of infrastructure that is in the focus of regional development policy and therefore this is the channel through which regional development can enhance innovation diffusion the most.